Recent and Prospective Trends in Real Long-Term Interest Rates Fiscal Policy and other Drivers - Brook, Anne-Marie (OECD Economics Department Working Papers, 2003)
This paper documents some features of recent trends in bond yields and discusses the drivers of these trends. This includes a discussion of the relationship between fiscal balances and interest rates -- with a summary of key empirical results from the literature provided in the Appendix. The main points to emerge from this analysis are as follows. First, cyclical and portfolio-allocation factors seem to have been the main driving forces behind the decline in long-term real interest rates over 2000-2003. However, in some European countries, declining (inflation, exchange-rate, and sovereign) risk premia suggest that the equilibrium real interest rate may now be somewhat lower. Second, the weight of recent evidence suggests a causal relationship from fiscal positions to long-term interest rates, at least for the United States. Thus, the actual and projected deterioration in US fiscal positions might have contributed to the recent rise in bond yields, although part of the ...